Higher degree of dysfunctional attitudes and beliefs and higher scores of frustration intolerance in women with unsuccessful weight loss - Tepšić Ostojić, Vesna; Stojanović, Zvezdana; Mraović, Tatjana; Mraović, Tatjana; Ristić Medić, Danijela (Vojnosanitetski pregled, 2024)
Background/Aim. Obesity is a chronic and relapsing condition, and since recently, it has been considered a global epidemic. Current guidelines for tripartite treatment of obesity emphasize a program of lifestyle modifications such as medical nutrition therapy, aerobic exercise, and behavioral intervention. The aim of the study was to evaluate whether specific psychological factors (general attitudes and beliefs and frustration tolerance) could be predictors of successful weight loss, i.e., factors that can be further addressed as part of the integrated therapy approach. Methods. A total of 84 consecutive overweight and obese female participants who were apparently healthy and homogeneous in age, level of education, and marital or employment status were prescribed the same medical nutrition therapy protocol as a single six-month therapeutic intervention. Prior to starting the therapy, the General Attitude and Belief Scale (GABS) and the Frustration Discomfort Scale (FDS) were administered. The participants were divided into two groups: successful (group A) and unsuccessful (group B). Group A, or the successful group [with the mean body mass index (BMI) ± standard deviation (SD) of 24.1 ± 5.81 kg/m2], consisted of 40 participants who have reached the corresponding loss, i.e., they lost ≥ 10% of the starting body weight (BW). Group B, or the unsuccessful group (with the mean BMI ± SD of 28.51 ± 2.74 kg/m2), consisted of 44 participants who have not reached the corresponding loss, i.e., they lost < 10% of the starting BW. Results. Participants in group B had significantly higher scores (p < 0.05) on the GABS subscales for the Need for Approval, Need for Comfort, and Other Downing. A statistically significant difference between groups (p < 0.05) was shown for FDS subscales of Emotional Intolerance, Entitlement, and Achievement Frustration. Conclusion. Results of our study showed that participants who were unsuccessful in medical nutrition therapy had a higher degree of dysfunctional attitudes and beliefs and higher scores of frustration intolerance when compared to successful participants. The recommendation, based on our results, would be to include psychotherapeutic techniques in the integrative obesity treatment, aimed at cognitive changes and increasing frustration tolerance.